Biodiesel synthesis using clinoptilolite-Fe3O4-based phosphomolybdic acid as a novel magnetic green catalyst from salvia mirzayanii oil via electrolysis method: Optimization study by Taguchi method. Issue 5 (October 2021) - Helmi, Maryam; Ghadiri, Mahdi; Tahvildari, Kambiz; Hemmati, Alireza
Abstract: Objective of current study is the synthesis of biodiesel from salvia mirzayanii oil using phosphomolybdic acid (H3 PMo12 O40, HPA) supported on the clinoptilolite-Fe3 O4 . The prepared catalyst properties were determined by different analyses including FESEM, EDX, TEM, FTIR, and VSM, and its performance was studied in the process of biodiesel production. Four key factors effects like reaction time, catalyst weight, methanol to oil molar ratio, and temperature were investigated and optimized by the Taguchi method. In this method, the significance of effective factors on the biodiesel yield is controlled by analysis of variance (ANOVA). The highest biodiesel yield was found 80% at operating conditions of 0.5 wt% HPA/clinoptilolite-Fe3 O4 catalyst, methanol/oil ratio of 12:1, and temperature of 75 °C at 8 h. The GC-MS analysis identified the fatty acid profile of salvia mirzayanii oil and biodiesel, the FTIR spectrum was performed to ensure biodiesel formation from the final product. The H NMR analysis compared the properties of oil and biodiesel. The physicochemical properties of the produced biodiesel revealed that the biodiesel has the same properties as the diesel. Also, it can be deduced that the synthesized biodiesel from salvia mirzayanii oil via electrolysis method is an economic and suitable method to produce biodiesel. Graphical Abstract: ga1 Highlights: HPA/clinoptilolite-Fe3 O4 as a new magnetic catalyst for biodiesel production. Using Salvia mirzayanii oil as a non-edible feedstock for biodiesel production. Optimization of the trans-esterification reaction using Taguchi technique. Electrolysis method with graphite electrodes was used to produce biodiesel. Catalyst hold its performance after using 4-times in trans-esterification reaction.